Effects of Vapocoolant Spray Prior to SC LMWH Injection: An Experimental Study. (February 2021) - Unal, Nursemin; Tosun, Betul; Aslan, Ozlem; Tunay, Servet
The aim of this study was to evaluate the effects of vapocoolant spray administration prior to subcutaneous (SC) low molecular weight heparin injection on local ecchymosis, hematoma, and pain. This randomized controlled study was carried out on 64 patients ( n = 128 injections) in an orthopedics and traumatology clinic. After randomization, vapocoolant spray and then heparin injection was applied on one arm. The second necessary dose of heparin was applied to his or her other arm as a placebo by a water spray. Then, the pain of the patients was assessed. After 2 days, ecchymosis and hematoma were evaluated. Significant lower pain scores were determined in applications in which the vapocoolant spray was used. There was no statically significant difference between the mean diameter values of ecchymosis in both arm groups. There was no hematoma on the injection site after injections. However, this method did not create any significant reductive effect on ecchymosis. Nurses are advised to take advantage of vapocoolant spray effects prior to SC heparin injection.